Stany Krytyczne Nierównomiernie Ogrzanych Perforowanych Płyt Kolistych - Klemm, P. (Engineering Transactions, 1970)
Here is presented a discussion of the stability problem of preliminarily bent circular perforated plates, perpendicular to which the motion of heat takes place. The problem is considered withinthe framework of the geometrically nonlinear, but physically linear theory.The solution is found by means of the energy method. Two critical states are distinguished and the parameters characterizing the above states are determined. A numerical example is given.